Exploring English as a Foreign Language Students’ Perspectives on Foreign Language Speaking Anxiety - Chicho, Kanar Z.H. (Mağallaẗ ğāmiʻaẗ Ğīhān- Arbīl li-l-ʻulūm al-insāniyyaẗ wa-al-iğtimāʻiyyaẗ, 2025)
Anxiety is a negative inward feeling that includes a sense of unease, stress, and hesitation. Anxiousness also has a psychological impact on an individual’s mental health. Thus, it can affect an individual’s academic performance. Therefore, anxiety is highly assessed in the fields of education and psychology. Psychologists differentiate several types of anxiety. Speaking anxiety is one of them. Language anxiety occurs while speaking a foreign language. It has consequences in learning a language. This study examines English as a foreign language students’ perception of foreign language speaking anxiety at the Faculty of Education-Tishk International University in the academic year 2022–2023. The present study answers the following inquiries: Students’ anxiety during speaking sessions in the class, the reasons for having anxiety, and the situations in which the students feel uncomfortable. A descriptive quantitative research design has been implemented, and an online survey was designed to determine the reasons and conditions for anxiety in speaking classes. The survey was sent to 80 Education Faculty students, who had 8 h of weekly speaking classes. Due to easy access, convenience sampling was implemented in the data collection. The researcher analyzed the data using Minitab 19. One-sample t-tests and analyses of variance areused. Results of data analyses showed that speaking a foreign language in front of the class is exclusively the source of anxiety. Based on the sufficient impact of language anxiety in speaking class, future studies could find strategies for decreasing language anxiety, like tailored anxiety management techniques.